Antibody-Drug Conjugates in Breast Cancer: Spotlight on HER2. Issue 6 (November 2022) - Abelman, Rachel Occhiogrosso; Medford, Arielle; Spring, Laura; Bardia, Aditya
Abstract: Antibody-drug conjugates (ADCs) are composed of monoclonal antibodies linked to a cytotoxic payload, enabling targeted delivery of more potent chemotherapy. In the past decade, there has been rapid development of ADCs aimed at different types of breast cancer. The success of the monoclonal antibody trastuzumab has led to the evolution of several ADCs targeting HER2-positive breast cancer. Trastuzumab-emtansine, the first approved ADC targeting HER2-positive breast cancer, has become standard of care for patients with high-risk early-stage HER2-positive breast cancer who have residual disease after neoadjuvant chemotherapy. More recently, the observation of the bystander effect, in which ADCs target both antigen-positive cells and adjacent antigen-negative cells, has led to the reclassification of "HER2-low" breast cancer and the development of trastuzumab-deruxtecan to target this population. This article reviews the history of HER2-directed ADCs in breast cancer as well as ongoing ADCs in development.